MO735INTERPLAY BETWEEN GDF-15 AND LEFT VENTRICULAR HYPERTROPHY IN END-STAGE RENAL DISEASE PATIENTS ON DIALYSIS. (29th May 2021) - Coimbra, Susana; Catarino, Cristina; Faria, Maria do Sameiro; Lopes Nunes, José Pedro; Rocha, Susana; Valente, Maria João; Rocha-Pereira, Petronila; Bronze-da-Rocha, Elsa; Bettencourt, Nuno; Beco, Ana; Homem Melo Marques, Sofia; Oliveira, José Gerardo; et al.
Abstract: Background and Aims: Cardiovascular disease (CVD) is the major cause of mortality and morbidity in chronic kidney disease (CKD), especially in end-stage renal disease (ESRD) patients. Left ventricular hypertrophy (LVH) is a common cardiovascular complication in CKD. Growth differentiation factor (GDF)-15 increases in tissue injury and inflammatory states associated with cardiometabolic risk. GDF-15 and N-terminal pro B-type natriuretic peptide (NT-proBNP) are both synthesized by cardiomyocytes and may be associated with cardiorenal dysfunction. Our aim was to study the association of GDF-15 with LVH in ESRD patients on dialysis. Method: This study included 196 ESRD patients on dialysis (hemodiafiltration and high-flux hemodialysis). Left ventricular mass (LVM) was evaluated through echocardiographic studies, corrected for body surface area and the values are presented as LVM index (LVMI). LVH was defined by a value of LVMI > 115 g/m2 in men and > 95 g/m2 in women. Patients were divided into two groups - LVH (n=131) and non-LVH (n=65). LVMI, clinical and analytical variables (age, body mass index, dialysis vintage, dialysis adequacy, GDF-15, NT-proBNP and pentraxin (PTX) 3 were evaluated. Results: ESRD patients with LVH presented significantly higher levels of NT-proBNP and GDF-15, and a trend towards higher PTX3 values. In LVH patients, GDF-15 correlated positively and significantly with NT-proBNP and PTX3; LVMI correlated positively and significantly with pro-BNP and PTX3 levels; pro-BNP correlated significantly and positively with PTX3. Conclusion: Our data show that in ESRD patients on dialysis with LVH, GDF-15 is raised and shows a strong association with NT-proBNP, PTX3 and LVMI. Further studies are needed to clarify if the rise in GDF-15 is a cause or a consequence of LVH development. Acknowledgments: This work was supported by Applied Molecular Biosciences Unit-UCIBIO, financed by national funds from FCT/MCTES (UIDB/04378/2020), by North Portugal Regional Coordination and Development Commission (CCDR-N)/NORTE2020/Portugal 2020 (Norte-01-0145-FEDER-000024) and by REQUIMTE-Rede de Química e Tecnologia-Associação in the form of a researcher (S. Rocha) – project Dial4Life co-financed by FCT/MCTES (PTDC/MEC-CAR/31322/2017) and FEDER/COMPETE 2020 (POCI-01-0145-FEDER-031322).